Do the project manager's soft skills foster knowledge sharing? - Avença, I. (2024)
In the realm of project management, the significance of soft skills, including communication, leadership, and problem-solving, has been acknowledged as pivotal to project success. Furthermore, the role of knowledge management within projects has emerged as another critical determinant of performance enhancement. This entails disseminating best practices, lessons learned, and insights garnered throughout the project lifecycle. Thus, the Project Manager's role acts as a catalyst, cultivating an environment that promotes effective knowledge sharing. The primary objective of this study is to explore the relationship between project manager soft skills and knowledge sharing within project environments. Additionally, considering the acknowledged impact of organizational culture and environment on knowledge sharing practices, this research aims to examine the moderating effect of organizational culture in shaping the relationship between soft skills and knowledge sharing effectiveness within project contexts. A questionnaire involving project team members was conducted to find answers to these questions. Findings reveal the project manager leadership was positively associated with knowledge sharing among project management team members. This conclusion innovatively connects the importance of soft skills in fostering knowledge sharing within project teams. It places a significant emphasis on the project manager's leadership skills assigning them a key responsibility. Additionally, moderation analysis showed that knowledge creation and knowledge capture strengthened the relationship between project manager's problem-solving skills and knowledge management environment. This underscores the role of a robust organisational culture in supporting knowledge sharing, thereby enhancing the connection between problem-solving abilities and explicit knowledge sharing.